An Analysis of Spiritual Intelligence with Self-Esteem of Chronic Kidney Disease (CKD) Patients at Cut Meutia Public Hospital, North Aceh - Wawan Supandi; Erna Masdiana (Jurnal Kesehatan Akimal, 2021)
Chronic Kidney Disease (CKD) with hemodialysis therapy can cause a decrease in organ function so that it affects the psyche, such as self-esteem. Related to self-esteem, spiritual intelligence is an important indicator in finding the meaning of life. Ones who have spiritual intelligence will capable of facing life choices in any situation. The purpose of the study is to carry out and analyze the spiritual intelligence with the self-esteem of CKD patients. This study used an analytical method. The sampling was done using the purposive sampling technique with a sample of 50 CKD patients undergoing hemodialysis therapy. Statistical analysis is carried out using Correction Yates. The results of this study showed that there is a relationship between spiritual intelligence and self-esteem of CKD patients at the Cut Meutia Public Hospital, North Aceh Regency with a p value = 0.018 which shows the number <0.05 so it can be concluded that the working hypothesis is accepted. The conclusion of this study is that spiritual intelligence can be used as an indicator to explain self-esteem because the higher spiritual intelligence, the higher the self-esteem of a person. Finally, the researcher is expected to develop further research on spiritual intelligence and other factors that affect the self-esteem of CKD patients.Chronic Kidney Disease (CKD) with hemodialysis therapy can cause a decrease in organ function so that it affects the psyche, such as self-esteem. Related to self-esteem, spiritual intelligence is an important indicator in finding the meaning of life. Ones who have spiritual intelligence will capable of facing life choices in any situation. The purpose of the study is to carry out and analyze the spiritual intelligence with the self-esteem of CKD patients. This study used an analytical method. The sampling was done using the purposive sampling technique with a sample of 50 CKD patients undergoing hemodialysis therapy. Statistical analysis is carried out using Correction Yates. The results of this study showed that there is a relationship between spiritual intelligence and self-esteem of CKD patients at the Cut Meutia Public Hospital, North Aceh Regency with a p value = 0.018 which shows the number <0.05 so it can be concluded that the working hypothesis is accepted. The conclusion of this study is that spiritual intelligence can be used as an indicator to explain self-esteem because the higher spiritual intelligence, the higher the self-esteem of a person. Finally, the researcher is expected to develop further research on spiritual intelligence and other factors that affect the self-esteem of CKD patients.